Comparative analysis of the dynamic behavior of structures equipped with cylindrical and spherical frictional bearings subjected to near-fault earthquakes - Auad, Gaspar (2024)
The effectiveness of seismic isolation in slender structures subjected to intense ground motion can be compromised by unwanted uplifting, a phenomenon often observed in frictional bearings featuring spherical sliding surfaces, such as the Friction Pendulum System (FPS) device. One solution to this issue involves incorporating a mechanism within the isolation devices to prevent uplifting. This study introduces an innovative numerical formulation for the tension-restraint Friction Pendulum isolator, referred to as the XY-FP bearing, which integrates complete frictional coupling and accounts for large displacements. Unlike conventional designs, the XY-FP bearing employs cylindrical sliding surfaces to achieve its isolation mechanism. Two structural models were created to investigate the dynamic behavior disparities between isolation systems utilizing cylindrical versus spherical frictional isolators. The models represent a single-story base-isolated building and a slender structure. Comparative analysis reveals that cylindrical frictional isolators exhibit reduced maximum displacements and increased sensitivity to ground motion directionality. Notably, using cylindrical frictional isolators can substantially increase maximum inter-story drifts and maximum absolute accelerations. Evaluation of the dynamic response of the slender building demonstrates the capacity of XY-FP bearings to mitigate undesired bearing uplifting effectively. However, the tensile forces generated by the isolators may surpass the magnitude of the static vertical load due to the superstructure's self-weight. Extending the isolated period is one potential strategy for alleviating the uplift magnitude or maximum tensile force.